KEDUDUKAN MEMORANDUM OF UNDERSTANDING (MOU) DALAM HUKUM PERJANJIAN DI INDONESIA - Aria Fikry Adriansyach (2024)
The MoU or Memorandum of Understanding is an initial agreement made based on the consensus of relevant parties, whether in writing or orally. Although not explicitly regulated in Indonesian contract law, especially in the Civil Code, some consider the MoU as something simple and easily revocable. This research specifically explores the legal position and consequences related to the creation of MoU. The research method used is normative law with a case study approach and legal framework. The results show that the MoU can be considered valid and binding as long as it fulfills the elements of a valid agreement. Furthermore, the MoU can be used as evidence in court in cases of contract violations. The MoU considered equivalent to a formal contract as long as it contains clauses regarding the rights and obligations of the parties and meets the elements of a valid agreement. Thus, the MoU holds significant legal weight and can serve as a strong foundation in the context of Indonesian law.